A new species of Mimela Kirby, 1825 from Laos with comments on M. gressitti (Frey, 1970), comb. n. (Coleoptera: Scarabaeidae: Rutelinae) - A.M. Prokofiev (Кавказский энтомологический бюллетень, 2018)
A new species, Mimela cupidinea sp. n., similar to M.  anopunctata (Burmeister, 1855) and M.  nigrosellata Ohaus, 1913, is described from Laos. All three species have small size (8–11 mm) and weakly expressed prosternal process. The prosternal process of these species is similar to that in the subgenus Rhombonyx Hope, 1837, which however includes large species (14–21  mm) with absolutely differ habitus. Externally Mimela cupidinea sp. n. differs from M. anopunctata and M.  nigrosellata in the completely beaded pronotal base and compressed from front to back prosternal process (which laterally compressed in both compared species) with more expressed additional small tooth near the posteroir margin. The structure of genitalia is similar to those in M. nigrosellata and differs from M. anopunctata by almost symmetrical parameres with a weakly impressed ventral contour. Parameres of Mimela cupidinea sp.  n. (in  contrast with M.  nigrosellata) are shorter than phallobase (phallobase is more than 2 times longer than parameres in a new species and less than 2 times longer in M. nigrosellata) and with gentle and evenly impressed ventral margin (with two distinct emarginations in M. nigrosellata). This new species also differs from both compared ones by visibly less curved in lateral view aedeagus. Anomala gressitti Frey, 1970 from Vietnam is transferred to the genus Mimela. The new combination is proposed: Mimela gressitti (Frey, 1970), comb. n. (from Anomala Samouelle, 1819). Differences between this species and M. krasava Prokofiev et Zorn, 2016 are specified.